Prognostic Value of β1 Adrenergic Receptor Autoantibody and Soluble Suppression of Tumorigenicity-2 in Patients With Acutely Decompensated Heart Failure - Sun, Yanxiang; Feng, Li; Hu, Bing; Dong, Jianting; Zhang, Liting; Huang, Xuansheng; Yuan, Yong (Frontiers in Cardiovascular Medicine, 2022)
Background: Both β1 adrenergic receptor autoantibody (β1-AA) and soluble suppression of tumorigenicity-2 (sST2) take a role in the pathological remodelling of heart failure. However, limited studies investigated the correlation between the expression of β1-AA and sST2 in patients with acutely decompensated heart failure (ADHF). Objective: To explore the correlation between β1-AA and sST2, and evaluate their prognostic value in patients with ADHF. Methods: Patients who were admitted for ADHF were included. N-terminal pro-brain natriuretic peptide (NT-proBNP), sST2 and β1-AA in blood samples were tested at hospital admission and then followed up for assessing outcomes. Pearson correlation analysis was used to explore the correlation between β1-AA and sST2. The effects of β1-AA, sST2 or the combination of them on the all-cause mortality of patients with ADHF were assessed by Multivariate Cox regression analysis. Results: 96 ADHF patients and 96 control populations were enrolled. The β1-AA was significantly higher in ADHF than in the control group (0.321±0.06 vs 0.229±0.04, P=0.000). Pearson correlation analysis showed that β1-AA was positively correlated with sST2 (r=0.593), NT-proBNP (r=0.557), Procalcitonin (r=0.176) and left ventricular end-diastolic diameter (r=0.315), but negatively correlated with triglycerides (r=-0.323) and left ventricular ejecton fraction (r=-0.430) (all P <0.05) in ADHF. ADHF patients complicated with both high β1-AA and sST2 showed the highest all-cause mortality during an average of 25.5 months of follow-up. Multivariate Cox regression showed the combination of both high β1-AA and sST2 independently correlated with all-cause mortality after adjustment for other risk factors (hazard ratio 3.348, 95% confiedenc interval 1.440 to 7.784, P=0.005). After adding with β1-AA and sST2, the area under the curves for the prognostic all-cause mortality could increase from 0.642 to 0.748 (P=0.011). Conclusion: The β1-AA is positively correlated with sST2 in patients with ADHF. Elevated plasma β1-AA and sST2 level in ADHF patients is associated with poorer prognoses.